Dual-Functional Lithiophilic/Sulfiphilic Binary-Metal Selenide Quantum Dots Toward High-Performance Li–S Full Batteries - Huang, Youzhang; Lin, Liang; Zhang, Yinggan; Liu, Lie; Sa, Baisheng; Lin, Jie; Wang, Laisen; Peng, Dong‑Liang; Xie, Qingshui (Nano-Micro Letters, 2023)
The commercial viability of lithium–sulfur batteries is still challenged by the notorious lithium polysulfides (LiPSs) shuttle effect on the sulfur cathode and uncontrollable Li dendrites growth on the Li anode. Herein, a bi-service host with Co-Fe binary-metal selenide quantum dots embedded in three-dimensional inverse opal structured nitrogen-doped carbon skeleton (3DIO FCSe-QDs@NC) is elaborately designed for both sulfur cathode and Li metal anode. The highly dispersed FCSe-QDs with superb adsorptive-catalytic properties can effectively immobilize the soluble LiPSs and improve diffusion-conversion kinetics to mitigate the polysulfide-shutting behaviors. Simultaneously, the 3D-ordered porous networks integrated with abundant lithophilic sites can accomplish uniform Li deposition and homogeneous Li-ion flux for suppressing the growth of dendrites. Taking advantage of these merits, the assembled Li–S full batteries with 3DIO FCSe-QDs@NC host exhibit excellent rate performance and stable cycling ability (a low decay rate of 0.014% over 2,000 cycles at 2C). Remarkably, a promising areal capacity of 8.41 mAh cm−2 can be achieved at the sulfur loading up to 8.50 mg cm−2 with an ultra-low electrolyte/sulfur ratio of 4.1 μL mg−1. This work paves the bi-serve host design from systematic experimental and theoretical analysis, which provides a viable avenue to solve the challenges of both sulfur and Li electrodes for practical Li–S full batteries. Highlights: 1 A bi-service host with lithiophilic/sulfiphilic Fe2CoSe4 quantum dots embedded in three-dimensional ordered nitrogen-doped carbon skeleton is elaborately developed for both the sulfur cathode and Li anode synchronously. 2 The highly dispersed Fe2CoSe4 quantum dots can not only act as a redox accelerator to promote the bidirectional conversion of LiPSs but also regulate the uniform Li plating/stripping to mitigate the growth of Li dendrite. 3 The assembled Li-S full batteries achieve excellent long-term cyclability and a remarkable areal capacity of 8.41 mAh cm2 at high sulfur loading of 8.50 mg cm2, and the pouch full battery also displays high capacity and cycling-stability at lean electrolyte condition.